2002
DOI: 10.1051/apido:2002038
|View full text |Cite
|
Sign up to set email alerts
|

Application of solid phase microextraction to evaluate traces of thymol in honey

Abstract: -The solid phase microextraction technique was tested for thymol evaluation in honey. Thymol can be present in honey as a residue of treatments against Varroa destructor Honey was sampled from apiaries treated with anti-Varroa products whose active ingredient is thymol. Thymol evaluation was done using the internal standard method; benzophenone and carvacrol were tested as internal standards/ the best results were obtained using benzophenone. The application of an alkaline hydrolysis was important for obtainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
3
1
Order By: Relevance
“…The obtained results were lower than those of Mattila and Otis (1999), Floris et al (2004), andAdamczyk et al(2005). However, they were higher than those obtained by Piasenzotto et al (2002), Donders and Cornelissen, (2005).…”
Section: Thymol Residues In Honeycontrasting
confidence: 61%
See 1 more Smart Citation
“…The obtained results were lower than those of Mattila and Otis (1999), Floris et al (2004), andAdamczyk et al(2005). However, they were higher than those obtained by Piasenzotto et al (2002), Donders and Cornelissen, (2005).…”
Section: Thymol Residues In Honeycontrasting
confidence: 61%
“…Residues of thymol found in honey collected from treated beehives ranged from 0.75 to 8.20 mg/kg for Apilife VAR (Adamczyk et al, 2005). Piasenzotto et al (2002) found that thymol content, evaluated by the SPE-GC method, ranged between 0.02 mg/kg and 0.91 mg/kg in honey samples collected from hives that had been treated with a thymol-based acaricides.…”
Section: Thymol Residues In Honeymentioning
confidence: 97%
“…Solid phase micro extraction (SPME)/Gas chromatography (GC)/Mass spectrometry (MS) technique has been used for various purposes in honey research such as pesticide residue analysis (Volante et al. , 1998, 2001), detection of acaricides residues (Piasenzotto et al. , 2002) and for determination of authenticity (Ruoff & Bogdanov, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…When identification of defects is considered, the sensory analysis of honey consents the recognition of contamination with foreign substances such as mothballs (p-diclorbenzene), essential oils (thymol), repellents (benzaldehyde), smell and taste of smoke, thymol, metallic taste, etc. (28,35). Higher-quality unifloral honey is honey which, with regard to the specific features of odour, taste, appearance, and tactile properties, is as close as possible to the hypothetical honey "standard", obtained entirely from the respective plant species (27).…”
Section: Authenticity Of Honeymentioning
confidence: 99%